2015
DOI: 10.1093/jac/dkv054
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal mode of action of bedaquiline

Abstract: Challenge with bedaquiline results in an electroneutral uncoupling of respiration-driven ATP synthesis. This may be a determinant of the bactericidal effects of bedaquiline, while ATP depletion may be a determinant of its delayed onset of killing. We propose that bedaquiline binds to and perturbs the a-c subunit interface of the Fo, leading to futile proton cycling, which is known to be lethal to mycobacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
242
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(261 citation statements)
references
References 32 publications
19
242
0
Order By: Relevance
“…2 C and D). TMC207 (1) is thought to target the ATP synthase in M. tuberculosis, but in recent work, it has also been proposed to act as an uncoupler, targeting again the ATP synthase (45). However, there is expected to be a significant protonophore contribution to its activity because clofazimine (17) (not thought to target the ATP synthase) and TMC207 (1) have almost identical logP, pK a , logD, and computed charge values (at pH 7.4) ( Table 1), even though the chemical structures are completely different.…”
Section: Resultsmentioning
confidence: 99%
“…2 C and D). TMC207 (1) is thought to target the ATP synthase in M. tuberculosis, but in recent work, it has also been proposed to act as an uncoupler, targeting again the ATP synthase (45). However, there is expected to be a significant protonophore contribution to its activity because clofazimine (17) (not thought to target the ATP synthase) and TMC207 (1) have almost identical logP, pK a , logD, and computed charge values (at pH 7.4) ( Table 1), even though the chemical structures are completely different.…”
Section: Resultsmentioning
confidence: 99%
“…The F 1 F 0 ATPase is the target of bedaquiline, a novel antibiotic for the treatment of tuberculosis (50,51). The mechanism of action has been thought to be due to depletion of available energy currency (52); however, more recent analysis has revealed that it uncouples cellular respiration from ATP synthesis, resulting in a futile proton cycle that is linked to cell death (53). The degree of respiratory acceleration caused by knockout of the F 1 F 0 catalytic domain in E. coli in our study (Fig.…”
Section: Bacteriostatic Alterations To the Metabolome Correspond To Rmentioning
confidence: 99%
“…333 A role for oxidative stress from the production of H 2 O 2 in the antibacterial mode of action of 334 PANI is supported by a) the supersensitivity of E. coli ΔkatG, which is unable to scavenge 335 endogenous H 2 O 2 and respond to the oxidative stress, and b) the decreased sensitivity of E. coli 336 342 based mechanism of action for PANI is derived from the greater sensitivity of the E. coli ΔiscS 343 mutant, which is unable to modify DNA for protection against oxidative stress . 344 The supersensitivity of the Spy mutant suggests that at least some of the damage is occurring in 345 Hards et al, 2015). There was evidence to imply damaged proteins may accumulate in the 358 periplasm following P3ABA exposure due to its proximity to the ETC and were inferred to 359 happen based on the insensitivity of the Spy mutant (which was hypothesised to have 360 upregulation of an additional extracytoplasmic stress response resulting in pre-adaption to 361 P3ABA action) (Raivio & Silhavy, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The decreased activity of P3ABA in anaerobic conditions 570 suggests that in rich media the antimicrobial activity of P3ABA involves a small amount of ROS 571 production. Uncoupling activity, such as what is postulated to occur during P3ABA action, 572 causes futile cycling, which is associated with increased oxygen consumption and production of 573 ROS (Adolfsen & Brynildsen, 2015;Hards et al, 2015). Therefore, the minor role of induction 574 of oxidative stress in P3ABA antimicrobial action may be due a downstream consequence of 575 uncoupling electron transport from ATP synthesis.…”
Section: B)mentioning
confidence: 99%